Professional Liability Insurance as an Alternative to Notary Legal Protection from the Legal Consequences of Insolvency Related to Errors in Making Authentic Deeds - Natasya Riesta Sivapramesti (Universitas Muhammadiyah Purwokerto, 2023)
According to Law 2 /2014 concerning amendments to Law 30/2004, notaries are public officials who have the authority to make authentic deeds and other authorities. Furthermore, authentic deeds are evidence with perfect strength in court, as long as it complies with the regulation. Therefore, a notary's mistakes in doing an authentic deed can cause loss to the service user. The notary can be sued for compensation and insolvency if they cannot compensate for those losses due to their financial limitation. This issue raises questions regarding the legal impacts of an insolvency decision on a notary and whether professional liability insurance can protect a notary from the legal impact of an insolvency decision on a notary. From this normative juridical research, the authors conclude that first, insolvency causes a notary to their position as a public official, and second, a notary can use professional liability insurance as a risk transfer mechanism. Keywords: insolvency; liability; insurance; law; notary.